2007
DOI: 10.1590/s0034-89102007000100004
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and risk of oral cancer: a case-control study in São Paulo, Brazil

Abstract: OBJECTIVE:To analyze the association between dietary patterns and oral cancer. METHODS:The study, part of a Latin American multicenter hospital-based casecontrol study, was conducted in São Paulo, Southeastern Brazil, between November 1998 and March 2002 and included 366 incident cases of oral cancer and 469 controls, frequency-matched with cases by sex and age. Dietary data were collected using a food frequency questionnaire. The risk associated with the intake of food groups defined a posteriori, through fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
1
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 17 publications
7
39
1
13
Order By: Relevance
“…groups [40,46,157,169]. However, there have been few studies which showed a significant survival benefit in favor of elective neck dissection in oral carcinoma patients with clinically N0 neck [36,62,76,94,170]. Among prospective randomized trials, only the study by Kligerman et al showed evidence of a statistically significant disease-free survival benefit of elective neck dissection over a policy of observation [79] (Table 5 and Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…groups [40,46,157,169]. However, there have been few studies which showed a significant survival benefit in favor of elective neck dissection in oral carcinoma patients with clinically N0 neck [36,62,76,94,170]. Among prospective randomized trials, only the study by Kligerman et al showed evidence of a statistically significant disease-free survival benefit of elective neck dissection over a policy of observation [79] (Table 5 and Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…They however suggested concurrent neck treatment with the surgical extirpation of the primary tumor if the tumor depth is more than 4mm or if the patient cannot be regularly followed-up. However, a few retrospective studies have reported on the survival benefit of elective neck dissection in oral carcinoma with clinical N0 neck [37,62,76,94]. It has also been reported that the survival rate of patients with oral carcinomas will reduce by 50% once there is a palpable cervical lymph node [42,52,87,132].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations